2011
DOI: 10.3399/bjgp11x606636
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing ventilation in homes of children with asthma: pragmatic randomised controlled trial

Abstract: BackgroundFew robust studies have tested whether enhancing housing also improves health. AimTo evaluate the effectiveness of installing ventilation systems, and central heating where necessary, in the homes of children with moderate or severe asthma. Design and settingPragmatic randomised controlled trial (RCT) in homes within Wrexham County Borough, Wales, UK. MethodA pragmatic RCT was carried out, of a tailored package of housing improvements providing adequate ventilation and temperature, following inspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…11 The analysis estimates the cost of a single-point improvement in the PedsQL asthmaspecific quality-of-life score at £234. At baseline, the median reported asthmarelated quality-of-life score was 67, with a lower quartile of 56 and an upper quartile of 79; 12 months later, parents of children in the intervention group reported a median score of 76, with a lower quartile of 64 and an upper quartile of 87.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 The analysis estimates the cost of a single-point improvement in the PedsQL asthmaspecific quality-of-life score at £234. At baseline, the median reported asthmarelated quality-of-life score was 67, with a lower quartile of 56 and an upper quartile of 79; 12 months later, parents of children in the intervention group reported a median score of 76, with a lower quartile of 64 and an upper quartile of 87.…”
Section: Discussionmentioning
confidence: 99%
“…After 12 months, the PedsQL showed a mean (adjusted) improvement of 8.65 in the intervention group and 1.58 in the control group. 11 The resulting difference of 7.07 (95% CI = 2.79 to 11.36) between groups is equivalent to a standardised effect size of 0.42.…”
Section: Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have generally found improvements against a wide range of respiratory outcomes [5, 11, 1620] related to warmth and energy efficiency works, particularly when targeted at households with inadequate warmth and where at least one member had a pre-existing respiratory condition. Platt et al [19] and Shortt and Rugkåsa [11] report both positive and negative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate ventilation needs to be built into energy efficient building projects, to avoid dampness, mould, radon, and other indoor pollutants. 13 Improved ventilation may enhance quality of life in asthma 14 and reduce transmission of some respiratory diseases in healthcare settings. Screens on windows and doors protect from vector borne diseases like malaria and reduce energy consumption from air conditioning and related greenhouse gases.…”
Section: Indoor Air Pollutionmentioning
confidence: 99%